Organic chemistry - Wade, L. G., 1947- (Upper Saddle River, NJ : Pearson Prentice Hall, 2010)
For two-semester courses in Organic Chemistry taken primarily by science and pre-health majors. Organized around functional groups, Wade$1 (Bs text is known for its student-oriented approach$1 (Bincorporating problem solving help, orientation features, and complete discussions of mechanisms. Wade explains concepts without taking the unnecessary short cuts that often lead to misconceptions. Wade$1 (Bs hallmark problem-solving approach includes unique strategies and hints to help students focus on the individual steps of each reaction and how they contribute to the overall reaction. Wade also employs the most pedagogically efficient method of mechanism boxes with its two-tiered approach: Mechanism and Key Mechanism Boxes. Because there are over 100 mechanisms boxed in every text, Wade delineates the 20 (3z(BKey(3y (Bmechanisms that comprise nearly all of the mechanisms students will encounter. This means Wade goes one additional and important step in helping students identify and grapple with the smallest number of the most important concepts to understand.s
Introduction and Review -- Structure and Properties of Organic Molecules -- Structure and Stereochemistry of Alkanes -- The Study of Chemical Reactions -- Stereochemistry -- Alkyl Halides: Nucleophilic Substitution and Elimination -- Structure and Synthesis of Alkenes -- Reactions of Alkenes -- Alkynes -- Structure and Synthesis of Alcohols -- Reactions of Alcohols -- Infrared Spectroscopy and Mass Spectrometry -- Nuclear Magnetic Resonance Spectroscopy -- Ethers, Epoxides, and Sulfides -- Conjugated Systems, Orbital Symmetry, and Ultraviolet Spectroscopy -- Aromatic Compounds -- Reactions of Aromatic Compounds -- Ketones and Aldehydes -- Amines -- Carboxylic Acids -- Carboxylic Acid Derivatives -- Condensations and Alpha Substitutions of Carbonyl Compounds -- hydrates and Nucleic Acids -- Amino Acids, Peptides, and Proteins -- Lipids -- Synthetic Polymers.
Includes index.
1
Keywords: Chemistry, Organic -- Textbooks